Fluorescence-guided lymphadenectomy in robot-assisted radical prostatectomy: the role of interventional radiology - Usai, Michele; Solinas, Emma; Fabio, Claudio; Madonia, Massimo; Tedde, Alessandro; Sica, Giacomo; Tamburrini, Stefania; Masala, Salvatore; Scaglione, Mariano (Frontiers in Radiology, 2025)
BackgroundBilateral extended pelvic lymph node dissection (ePLNR) is used in high-risk prostate cancer for assessing metastatic involvement and lymph node staging. Nevertheless, in patients with localized or locally advanced prostate cancer, loco-regional lymph nodes are not always metastatic. Based on this assumption, the aim of this study is to evaluate the potential of ePLND performed under fluorescence guidance after administration of the Indocyanine green (ICG)—Lipiodol mixture via embolization of the prostate arteries in order to identify metastatic lymph nodes, that are then confirmed by histopathology analysis.Materials and methodsAll participants underwent selective embolization of the prostatic arteries 24–48 h before the scheduled surgery. The embolization procedure involved the injection of 25 mg/ml ICG, distilled water, and Lipiodol adequately mixed. During ePLND, the “Firefly” mode integrated into the Da Vinci robotic system was used to assess fluorescence in loco-regional lymph nodes. The lymph nodes were harvested and sent for histopathological examination. Intraoperative fluorescence results, histopathological findings, and short-term postoperative complications were recorded and classified according to the Clavien-Dindo system. For statistical analysis, the Phi coefficient was used to assess the correlation between categorical variables.ResultsTen patients diagnosed with high-risk or unfavorable intermediate-risk PCa were included. All patients underwent radical robot assisted prostatectomy with ePLND within 48 h of prostate embolization using ICG-Lipiodol. Intraoperative fluorescence results, final histopathological findings and postoperative complications were recorded. The lymph nodes with positive fluorescence, after being analyzed separately, were confirmed to be as metastatic upon dedicated histopathological examination, while non-fluorescent lymph nodes were found to be negative for metastatic involvement. The phi coefficient was calculated to establish the degree of correlation between detection of green fluorescence by Firefly system and the positivity of lymph nodes for metastatic invasion at the histopathological analysis. The concordance assessed by phi correlation coefficient was 0.76, with a sensitivity of 100% (95% confidence interval).ConclusionAlthough preliminary, the results of this study demonstrate the potential of fluorescence-guided ePLND after ICG-Lipiodol administration for improving the identification of metastatic lymph nodes during Robotic-assisted radical prostatectomy RARP. Further studies are required to validate our findings with a larger group of patients.